The failure of Chinese peer-to-peer lending platforms: Finance and politics - Qing He; Xiaoyang Li (Bank of Finland, Institute for Economies in Transition (BOFIT), 2020)
We investigate the influence of financial and political factors on peer-to-peer (P2P) platform failures in China's online lending market. Using a competing risk model for platform survival, we show that large platforms, platforms with listed firms as large shareholders, and platforms with better information disclosure were less likely to go bankrupt or run off (platform owners abscond with investor funds). More importantly, failing platforms were much less likely to run off in advance of major political events, but more likely to declare bankruptcy or run off after such events. These effects are more pronounced for politically connected platforms, platforms operating in provinces where local officials have close ties with central government, and in provinces with better local financial conditions. Our study highlights the role of political incentives on government regulatory intervention in platform failures.
URN:NBN:fi:bof-202012152560
Keywords: G33; G21; G23; P26; 330; P2P platform failure; political interference; political connection; financial performance